Development of a naked eye CRISPR-Cas12a and -Cas13a multiplex point-of-care detection of genetically modified swine - Wang, Y.; Fu, L.; Tao, D.; Han, X.; Xu, B.; Deng, M.; Li, S.; Zhao, C.; Li, X.; Zhao, S.; Gong, P.; Yang, Y.; et al. (American Chemical Society, 2023)
The Rapid Visual CRISPR (RAVI-CRISPR) assay employs Cas12a and Cas13a enzymes for precise gene detection in a sample. However, RAVI-CRISPR is limited in single-tube multiplex detection applications due to the lack of specific single-strand (ss) DNA-fluorescently quenched (ssDNA-FQ) and RNA-fluorescently quenched (ssRNA-FQ) reporter cleavage mechanisms. We report the development of a sensitive and specific dual-gene Cas12a and Cas13a diagnostic system. To optimize the application for field testing, we designed a portable multiplex fluorescence imaging assay that could distinguish test results with the naked eye. Herein, dual gene amplified products from multiplex recombinase polymerase amplification (RPA) were simultaneously detected in a single tube using Cas12a and Cas13a enzymes. The resulting orthogonal DNA and RNA collateral cleavage specifically distinguishes individual and mixed ssDNA-FQ and ssRNA-FQ reporters using the green–red–yellow, fluorescent signal conversion reaction system, detectable with portable blue and ultraviolet (UV) light transilluminators. As a proof-of-concept, reliable multiplex RAVI-CRISPR detection of genome-edited pigs was demonstrated, exhibiting 100% sensitivity and specificity for the analysis of CD163 knockout, lactoferrin (LF) knock-in, and wild-type pig samples. This portable naked-eye multiplex RAVI-CRISPR detection platform can provide accurate point-of-care screening of genetically modified animals and infectious diseases in resource-limited settings.